Could futures markets help growers better manage coffee price risks in Costa Rica? - Hazell, Peter B. R. (International Food Policy Research Institute, 2000)
Costa Rican coffee farmers are almost fully exposed to world price variability. Yet, despite small farm sizes, specialization in coffee, and a marketing system that prolongs uncertainty and aggravates cash flow problems, this study finds that most farmers still manage their price risks surprisingly well. Farmers are able to forecast prices with comparable accuracy to the New York futures market. They have a favorable seasonal cash flow, ready access to credit, and are willing and able to bear risk. Within this context, the potential gains from using the New York futures market to provide forward price contracts at harvest are found to be modest.